2018
DOI: 10.1177/1090198117747659
|View full text |Cite
|
Sign up to set email alerts
|

Health Improvement and Educational Attainment in Secondary Schools: Complementary or Competing Priorities? Exploratory Analyses From the School Health Research Network in Wales

Abstract: Background. Implementing health improvement is often perceived as diverting resource away from schools’ core business, reflecting an assumption of a “zero-sum game” between health and education. There is some evidence that health behaviors may affect young people’s educational outcomes. However, associations between implementation of school health improvement and educational outcomes remains underinvestigated. Methods. The study linked school-level data on free school meal (FSM) entitlement, educational outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…This association was maintained in all models, adjusting for primary school FSM entitlement, secondary school FSM entitlement and both, strengthening in magnitude in the final model. Our previous analyses have shown that the FSM entitlement of a secondary school predicts the largest portion of variance in pupil attainment between schools (Littlecott et al , 2018). In this study, the discrepancy between the socioeconomic composition of a young adolescent’s primary and secondary school explained almost 30% of residual variance in mental wellbeing, after within‐school differences in socio‐demographics had been accounted for.…”
Section: Discussionmentioning
confidence: 97%
“…This association was maintained in all models, adjusting for primary school FSM entitlement, secondary school FSM entitlement and both, strengthening in magnitude in the final model. Our previous analyses have shown that the FSM entitlement of a secondary school predicts the largest portion of variance in pupil attainment between schools (Littlecott et al , 2018). In this study, the discrepancy between the socioeconomic composition of a young adolescent’s primary and secondary school explained almost 30% of residual variance in mental wellbeing, after within‐school differences in socio‐demographics had been accounted for.…”
Section: Discussionmentioning
confidence: 97%
“…A growing evidence base, however, indicates that health and educational attainment are synergistic rather than competing goals (Littlecott et al, 2018). Furthermore, education policy has increasingly diverged between the UK nations since devolution; in Wales, a number of recent policy developments have put support for health and well-being at the forefront of what schools are expected to do.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of these proposals is deep-seated in the influence of the Health Promoting Schools movement, created by the World Health Organization in the 1990s. It proposed a change in the system, with the integration of the health and education sectors, the establishment of adequate settings, and the effective participation of the school community (2)(3) .…”
Section: Introductionmentioning
confidence: 99%